Great expectations : the toddler years : everything you need to know about your 1-to 3-year-old - Jones, Sandy (New York : Sterling, 2011)
'Sterling's newest book in the acclaimed Great Expectations series covers every challenge parents and children face in the transition from baby to toddler, from toilet training and teeth brushing to language skills and healthy sleep habits, plus discipline, socialization, and play. Special sections on nutrition and childcare enrich the mix, along with insights to help parents become more flexible, responsive, patient, and creative'--
includes index
Keywords: Toddlers; Child rearing; Parenting